Aspectos estruturais e funcionais da comunidade de peixes demersais da Baía de Santos - SP - Rotundo, Matheus Marcos (Universidade Federal de São Carlos, 2020)
We assessed the structural and functional aspects of the Santos Bay demersal fish community through four sampling campaigns distributed quarterly between April and December 2017. In each campaign, six 30-minute bottom trawls were carried out at six predefined points equidistant at approximately 2km. We recorded the following data: salinity, conductivity, temperature, pH, dissolved oxygen and surface and bottom turbidity and as depth. Sediment samples were collected. The rainfall data for the previous four days and the day of the collection date were also recorded. We identified, measured,weighed and sexed each specimen visually annotating its degree of gonadal maturation. Data were evaluated in terms of numerical abundance and weight for the trophic and occupation guilds, Shannon index and its four weighted heuristic adaptations with two different functions (trophic and occupation) and one combining the previous two. The data analysis consisted of ANOVAs, having as factors the sampling points, bathymetric bands and both sides of the bay. Principal component analysis was also performed with abiotic data and canonical correspondence analysis with biotic and abiotic data. The ichthyofauna in the Santos Bay has a homogeneous composition, but differentiated from other sectors of the estuarine complex. Its richness is comparatively high, showing only seasonal variations. The ichthyofauna is composed of juveniles of species of economic and ecological importance. It presented high dominance both numerical and in weight, a large number of carnivorous, but with greater representation of numerical abundance and in weight of omnivores. The trophic guilds showed seasonal variations and segregation of body size by depth. Most species tolerate high salinity values, with patterns of spatial segregation by depth and seasonal by body size. The Shannon diversity index and its weighted heuristic versions showed only seasonal variations, related to the characteristics of the abiotic profiles of each climatic season. Weighted heuristic indices detected more significant differences between functional guilds. Thus, they resulted in a satisfactory statistical analysis for the interpretation of space-seasonal variations in functional diversity. The use of abundance data by weight showed to be more suitable for ecological interpretations, when compared to numerical abundance. Much of the behavior of the abiotic parameters is explained by its high synergy, as well as by the internal circulation, supply of rainwater drainage and the intrusion of adjacent marine waters. The structuring of the community is directly related to the seasonal variations of the abiotic parameters, where the hydrological cycle was the main responsible for the observed changes. Trophic guilds play an important role in structuring the community. Spatial variations by depth are responsible for the stratification of different variables. The ANOVAs referring to the locations, did not show significant differences for any of the dependent variables considered. Thus, management actions for the conservation of ichthyofauna in Santos Bay are necessary, due to fishing pressure and anthropological impacts.
Structural and functional aspects of the demersal fish community in Santos Bay – SP
Keywords: Ictiofauna; Baía de Santos; Estrutura de comunidade; Composição; Abundância; Diversidade funcional; Características abióticas; Desenvolvimento gonadal; Ichthyofauna; Santos Bay; Community structure composition; Abundance; Functional diversity; Abiotic parameters; Gonadal development; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS EXATAS E DA TERRA::OCEANOGRAFIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS EXATAS E DA TERRA::OCEANOGRAFIA::OCEANOGRAFIA BIOLOGICA::INTERACAO ENTRE OS ORGANISMOS MARINHOS E OS PARAMETROS AMBIENTAIS; CIENCIAS EXATAS E DA TERRA::OCEANOGRAFIA::OCEANOGRAFIA BIOLOGICA; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA::RECURSOS PESQUEIROS MARINHOS; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA::RECURSOS PESQUEIROS MARINHOS::MANEJO E CONSERVACAO DE RECURSOS PESQUEIROS MARINHOS